A highly sensitive electrochemiluminescence cytosensor for detection of SKBR-3 cells as metastatic breast cancer cell line: A constructive phase in early and precise diagnosis - Nasrollahpour, Hassan; Mahdipour, Mahdi; Isildak, Ibrahim; Rashidi, Mohammad-Reza; Naseri, Abdolhosein; Khalilzadeh, Balal (ELSEVIER ADVANCED TECHNOLOGY, 2021)
Ultrasensitive monitoring of cancer cells, especially metastatic ones, has a great interest in human medicine. Despite the early diagnosis of diseases, there is an essential need for any prediction in the severity of side effects for therapeutic outcomes like metastasis. Therefore, the inhibition of cancer cells metastasis to other organs is of utmost importance for cancer suffering patients. In this regard, we developed an electrochemiluminescence (ECL)-based cytosensor for the quantification of metastatic breast cancer cells, namely SKBR-3. Silica-based mesoporous materials have a great potential for application in ECL biosensors due to their high loading capacity and mechanical strength. Herein, a silica-based electrode was prepared via in situ electrosyntheses of mesoporous silica as an environmentally friendly approach. In this protocol, luminol (as luminophore) was combined with chitosan (as attachment biomolecule) to produce a stable lumino-composite film on the electrode surface. At the optimum experimental conditions, the lower limit of quantitation (LLOQ) and linear dynamic range (LDR) were obtained as 20 cells/mL and 20 to 2000 cells/mL, individually. The specificity was desirably examined in the presence of other breast cancer cell lines such as MCF-7 and MDA-MB-231, as a model of early-stage and invasive phases of breast cancer cells. The repeatability was successfully examined for five repetitive measurements and the acceptable relative standard deviation (RSD) was calculated as about 1.6% for 500 cells/mL. As a proof of concept, the presented cytosensor has a high ability to use in clinical laboratories for the detection and separation of metastatic cells via the combination with microfluidic systems.
Keywords: Electrochemiluminescence cytosensor; Breast cancer; Early-stage detection; Mesoporous silica; Biocompatible; SKBR-3 cells; QUANTUM DOTS; GOLD NANOPARTICLES; IN-SITU; BIOSENSOR; ELECTRODE; LUMINOL; ELECTROOXIDATION; NANOCOMPOSITES; ANTIBODIES; TOXICITY; Biophysics; Biotechnology & Applied Microbiology; Chemistry; Electrochemistry; Science & Technology - Other Topics